Identifikasi Cekungan Sedimen Lokasi Manifestasi Gas Alam Kampung Holtekamp Kota Jayapura Melalui Pemodelan Tiga Dimensi (3D) Berdasarkan Anomali Gravitasi GGMplus - Bangkit Sudrajad; Tatang Sutarman (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Natural gas is one of the natural resources that are abundant in Indonesia. Papua is one of the regions in Indonesia that has large potential reserves of natural gas, including Jayapura City. The existence of natural gas potential in Jayapura City is indicated by the presence of natural gas bursts that came out during the drilling process of the wells of residents of Holtekamp Village, Muara Tami District, Jayapura City. The gas burst incident that appeared in the Holtekamp Village area was not the first to occur in the Muara Tami District area but the presence of natural gas manifestations has also been found in West Koya. In relation to this, the author took the initiative to conduct geophysical research using the gravity method. This gravity method is used to determine the condition of the subsurface structure regionally. Based on 3D modeling based on GGMplus gravity anomalies, it was obtained that the natural gas manifestation area of ​​Holtekamp Village is in a coastal sedimentary basin and swamp with a depth of 500 meters. In addition, the results of 3D modeling also identified 1 other sedimentary basin with a depth of 1200 meters in the shallow sea area on the Holtekamp coast and 2 other sedimentary basins with depths of 1500 meters and 2500 meters in Youtefa Bay. Keywords: 3D Modeling; GGMplus, Gravity Method; Natural Gas;Sedimentary Basin